2005
DOI: 10.1161/01.res.0000171805.24799.fa
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Soluble Tissue Factor Is Released From Endothelial Cells in Response to Inflammatory Cytokines

Abstract: Inflammatory cytokines alter the hemostatic balance of endothelial cells (ECs). Alternatively spliced human tissue factor (asHTF), a soluble isoform of tissue factor (TF), has recently been detected in ECs, possibly contributing to procoagulability. Agonists regulating asHTF expression and release are yet unknown. This study examines the effect of TNF-alpha and IL-6 on the endothelial expression of both TF variants and delineates the impact of asHTF on the procoagulability of extracellular fluids. asHTF and TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
218
1
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(242 citation statements)
references
References 27 publications
10
218
1
13
Order By: Relevance
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].…”
supporting
confidence: 92%
See 4 more Smart Citations
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].…”
supporting
confidence: 92%
“…We observed that MP-TF activity in cancer patients with VTE is higher than in matched cancer patients without VTE. This finding strongly supports previous observations of a relationship between elevated MP-TF activity and VTE in patients with cancer from small studies of selected cancer patients [1,[4][5][6].It is interesting that the large majority of patients who develop VTE during chemotherapy have normal MP-TF activity, suggesting that an acute thrombotic event itself is not the cause of an elevated MP-TF activity. Our data point to a contribution of cancer cells themselves as (in) direct cause of elevated MP-TF activity and ask for novel studies better designed to study prospectively the relationship between chemotherapy, elevated MP-TF activity and venous thrombosis.…”
supporting
confidence: 90%
See 3 more Smart Citations